Quantification of biotic responses to rapid climatic changes around the Younger Dryas - a synthesis - Ammann, B; Birks, HJB; Brooks, SJ; Eicher, U; von Grafenstein, U; Hofmann, W; Lemdahl, G; Schwander, J; Tobolski, K; Wick, L (ELSEVIER SCIENCE BV, 2000)
To assess the presence or absence of lags in biotic responses to rapid climatic changes, we: (1) assume that the delta(18)O in biogenically precipitated carbonates record global or hemispheric climatic change at the beginning and at the end of the Younger Dryas without any lag at our two study sites of Gerzensee and Leysin, Switzerland; (2) derive a time scale by correlating the delta(18)O record from these two sites with the delta(18)O record of the GRIP ice core; (3) measure delta(18)O records in ostracods and molluscs to check the record in the bulk samples and to detect possible hydrological changes; (4) analyse at Gerzensee and Leysin as well as at two additional sites (that lack carbonates and hence a delta(18)O record) pollen, plant macrofossils, chironomids, beetles and other insects, and Cladocera; (5) estimate our sampling resolution using the GRIP time scale for the isotope stratigraphies and the biostratigraphies; and (6) summarise the major patterns of compositional change in the biostratigraphies by principal component analysis or correspondence analysis. We conclude that, at the major climatic shifts at the beginning and end of the Younger Dryas, hardly any biotic lags occur (within the sampling resolution of 8-30 years) and that upland vegetation responded as fast as aquatic invertebrates. We suggest that the minor climatic changes associated with the Gerzensee and Preboreal oscillations were weakly recorded in the biostratigraphies at the lowland site, but were more distinct at higher altitudes. Individualistic responses of plant and animal species to climatic change may reflect processes in individuals (e.g. productivity and phenology), in populations (e.g. population dynamics), in spatial distributions (e.g. migrations), and in ecosystems (e.g. trophic state). We suggest that biotic responses may be telescoped together into relatively short periods (50 to 150 years), perhaps disrupting functional interactions among species and thus destabilising ecosystems. (C) 2000 Elsevier Science B.V. All rights reserved.